A Dutch phase III randomized multicenter trial: whole brain radiotherapy versus stereotactic radiotherapy for 4–10 brain metastases. Issue 1 (1st February 2021) - Hartgerink, Dianne; Bruynzeel, Anna; Eekers, Danielle; Swinnen, Ans; Hurkmans, Coen; Wiggenraad, Ruud; Swaak-Kragten, Annemarie; Dieleman, Edith; van der Toorn, Peter-Paul; Oei, Bing; van Veelen, Lieneke; Verhoeff, Joost; et al.
Abstract: Background: The clinical value of whole brain radiotherapy (WBRT) for brain metastases (BM) is a matter of debate due to the significant side effects involved. Stereotactic radiosurgery (SRS) is an attractive alternative treatment option that may avoid these side effects and improve local tumor control. We initiated a randomized trial (NCT02353000) to investigate whether quality of life is better preserved after SRS compared with WBRT in patients with multiple brain metastases. Methods: Patients with 4–10 BM were randomized between the standard arm WBRT (total dose 20 Gy in 5 fractions) or SRS (single fraction or 3 fractions). The primary endpoint was the difference in quality of life (QOL) at 3 months post-treatment. Results: The study was prematurely closed due to poor accrual. A total of 29 patients (13%) were randomized, of which 15 patients have been treated with SRS and 14 patients with WBRT. The median number of lesions were 6 (range: 4–9) and the median total treatment volume was 13.0 cc 3 (range: 1.8–25.9 cc 3 ). QOL at 3 months decreased in the SRS group by 0.1 (SD = 0.2), compared to 0.2 (SD = 0.2) in the WBRT group ( P = .23). The actuarial 1-year survival rates were 57% (SRS) and 31% (WBRT) ( P = .52). The actuarial 1-year brain salvage-free survival rates were 50% (SRS) and 78% (WBRT) ( P = .22). Conclusion: In patients with 4–10 BM, SRS alone resulted in 1-year survival for 57% of patients while maintaining quality of life. Due to the premature closure of the trial, no statistically significant differences could be determined.